Representasi Kekerasan dalam Rumah Tangga pada Kumpulan Cerpen Kembang Selir Karya Muna Masyari - Wulandari, Yuyun; Israhayu, Eko Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This research departs from the depiction of domestic violence in literary works that cause a household to experience disharmony. On this basis, the purpose of this research is to describe domestic violence contained in literary works. This research is included in qualitative descriptive research with the object of research in the form of a description of domestic violence which is studied based on forms of domestic violence such as physical, psychological, sexual violence and domestic neglect. The book of short stories Kembang Selir by Muna Masyari published by the publisher DIVA Perss in 2023 was determined as a data source in conducting this research.. The research data was obtained from words, phrases, sentences, paragraphs, metaphors, dialogues, and monologues that contain descriptions of domestic violence in the short story collection book Kembang Selir by Muna Masyari. The data collection technique is carried out by reading, listening, and taking notes. Triangulation is used as a data validity technique in conducting research. Then, the analysis of research data uses three stages, namely: data reduction, data presentation, and data verification. The results of this study show that there are depictions of domestic violence in several short stories contained in the collection of short stories Kembang Selir by Muna Masyari, namely: 1) The short story